Implementation of the Grammatical Method in Making Arabic Sentence Patterns at MTs Ulumul Qur'an Teladan - Sonia Rekasharma; Zulkarnein Lubis (Al-Ulum: Jurnal Pendidikan Islam, 2022)
This study aims to find out how the process of learning Arabic by using grammatical methods in making Arabic sentence patterns at MTs Ulumul Qur'an Teladan. This research is a descriptive qualitative research using data collection techniques through observation, interviews, questionnaires and documentation. Data analysis was carried out through the stages of data collection, data reduction, display data and drawing conclusions. The validity of the data was tested by testing the validity of the data by extending attendance, increasing persistence, and triangulation, technical triangulation, and time triangulation. The results showed that: First, there are three stages of Arabic learning activities, namely opening activities, core activities and closing activities; Second, the grammatical method in making Arabic sentence patterns is implemented through three processes, namely the process of pronunciation and imitation, the process of translating and writing, the process of making Arabic sentence patterns properly and correctly in accordance with Arabic rules.